Defaulting among patients attending the central sexually transmitted disease clinic, Colombo and the impact of an intervention - Ariyaratne, K.A.M (My University, 2000)
The study was conducted in three phases. The first two phases were carried out as baseline surveys before developing the intervention programme.Phase, It was a retrospective study which included an analysis of clinic records of newly registered STD clinic patients for a period of one year to study the extent and the pattern of defaulting. Phase II had two components. These consisted of a comparative prospective study with a follow-up period of two months and a descriptive study of defaulters. These two components were conducted concurrently. The main objective of the phase II were to study factors associated with and reasons for defaulting. The third phase was to develop, implement and evaluate an intervention programme to reduce defaulting by clinic attendees. This study has demonstrated high default rate among patients attending the central STD clinic, Colombo which significantly improved following an intervention which consisted of a counseling session and distribution of an educational leaflet giving information about the importance of adequate follow-up care. It is recommended that medical officers should be more considerate and flexible when scheduling follow-up dates. A reception counter manned by well-trained staff will reduce the difficulties encountered by patients on attending the clinic. The results indicate the need for operational research to improve the quality of service delivery in STD clinics